Supramolecular Nanocomposites: Dual‐Functional Cholesteric Hydroxypropyl Cellulose Esters Chemically Linked to Gold Nanoparticles. Issue 4 (17th March 2016) - Ohlendorf, Peter; Dulle, Martin; Förster, Stephan; Greiner, Andreas
Abstract: Functionalization of metal nanoparticles with liquid crystal polymers (LCP) is attractive for the formation of supramolecular structures with unique physical properties. We discovered that the chemical linkage of a liquid crystalline thiolated cellulose ester (HPC‐MTP_80) to gold nanoparticles (AuNP) leads, by control of the supramolecular structure, to a novel concept for functional materials with practical applications. At a critical concentration ratio of only 1.7 mol % HPC‐MTP_80, on average, only single HPC‐MTP_80 functionalized AuNP exist, forming a LC phase. Pure HPC‐MTP_80 forms a cholesteric phase with a pitch in the range of visible light. The slow pitch formation enables usage as a protective sealing material. This property in combination with the temperature dependence of the pitch makes HPC‐MTP_80 a perfect sensor for temperature monitoring of sensitive products like valuable pharmaceutics. Even the presence of very small amounts of functionalized AuNP in the nanocomposite suppress the pitch formation in the range of visible light, providing access for a possible application as a sensitive AuNP detector. Abstract : The structure of a cholesteric liquid crystalline cellulose derivative can be most significantly modified when it is chemically attached to gold nanoparticles, which leads directly to practical applications. Variation of the ratio of components results in different nanocomposite structures with different thermal and optical properties. Thereby, the cellulose derivative can be used as a sensitive nanoparticle sensor and sealing material.